The Identity‐Location Binding Problem. (2nd December 2014) - Howe, Piers D. L.; Ferguson, Adam
Abstract: The binding problem is fundamental to visual perception. It is the problem of associating an object's visual properties with itself and not with some other object. The problem is made particular difficult because different properties of an object, such as its color, shape, size, and motion, are often processed independently, sometimes in different cortical areas. The results of these separate analyses have to be combined before the object can be seen as a single coherent entity as opposed to a collection of unconnected features. Visual bindings are typically initiated and updated in a serial fashion, one object at a time. Here, we show that one type of binding, location‐identity bindings, can be updated in parallel. We do this by using two complementary techniques, the simultaneous‐sequential paradigm and systems factorial technology. These techniques make different assumptions and rely on different behavioral measures, yet both came to the same conclusion.